Effect of Chitooligosaccharides on TLR2/NF-κB Signaling in LPS-Stimulated RAW 264.7 Macrophages - Mengting Zhao; Shurong Pang; Yiqing Gao; Ting Li; Hongrui Jiang (Molecules)
Chitooligosaccharides (COSs), degraded products of chitosan or chitin, are attracting growing interest owing to their low degree of polymerization (DP), high solubility, and prominent anti-inflammatory activity. However, the correlation between their structure and anti-inflammatory activities still needs to be explored. In this study, we use LPS-stimulated RAW 264.7 macrophages as an inflammatory model to systematically evaluate COS1–7 for their effects on inflammatory mediators and NF-κB signaling pathways. The results of Griess assay, ELISA, and real-time quantitative PCR show that COSs can inhibit the expression of NO, iNOS, and pro-inflammatory cytokines (IL-6, TNF-α, MCP-1 and IL-1β), thereby attenuating inflammatory signaling. Notably, chitohexaose (COS6) exhibits the most significant anti-inflammatory effect, reducing the mRNA levels of LPS-induced iNOS, IL-6, and IL-1β and the production of IL-6 and TNF-α by more than 50%. Transcriptome, western blotting, and real-time quantitative PCR analysis reveal that COSs can inhibit the activation of the NF-κB signal pathway by down-regulating TLR2 levels. Additionally, molecular docking confirms that COSs retard TLR2/4 dimerization and LPS recognition by TLR4, affecting downstream signaling cascades. In summary, this study provides a valuable insight into the potential anti-inflammatory mechanism of COSs and highlights the possible applications in human health promotion by modulating receptor-mediated signaling pathways.